1992
DOI: 10.1002/sca.4950140505
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation and dehydration of calcium sulphate dihydrate in solution studied by SEM

Abstract: The transformation of separate crystals of CaS04·2H20 (DH) into CaS04·0.5H20 (HR) in an aqueaus solution of H3P04 and H2S04 at 90-97°C was studied using a JSM-35CF SEM. The source DR and acids were reagent or eommereial (taken from the produetion of H3P04 by a wet process). DR was allowed to eonvert into HR and periodie samples of the suspension were drawn, filtered, and investigated in the solid phase by SEM. It was shown that the dehydration of reagent DH speeimens oeeurred through the reerystallization mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Different organics were tried, but 2-propanol was the one that was chosen. Use of acetone is reported in the literature, , but 2-propanol was found to achieve better results. The final dry samples were examined with XRD (Philips PW1710 X-ray diffractometer) as well as DSC (PerkinElmer PYRIS differential scanning calorimeter) for phase identification, and with SEM (JEOL-840A SEM, coupled with energy-dispersive X-ray spectrometer and digital imaging system) for morphology characterization.…”
Section: Methodsmentioning
confidence: 95%
“…Different organics were tried, but 2-propanol was the one that was chosen. Use of acetone is reported in the literature, , but 2-propanol was found to achieve better results. The final dry samples were examined with XRD (Philips PW1710 X-ray diffractometer) as well as DSC (PerkinElmer PYRIS differential scanning calorimeter) for phase identification, and with SEM (JEOL-840A SEM, coupled with energy-dispersive X-ray spectrometer and digital imaging system) for morphology characterization.…”
Section: Methodsmentioning
confidence: 95%
“…Previous research for a variety of solution compositions found that the DH to HH, DH to AH and HH to AH phase transformations typically proceeded via a dissolution-precipitation based mechanism (Austin et al, 1975;Azimi and Papangelakis, 2011;Beretka and Van Der Touw, 1989;Farrah et al, 2004;Hardie, 1967;Imahashi and Miyoshi, 1994;Kontrec et al, 2002;Müller et al, 2009;Sirota et al, 1992). Furthermore, it was found that an increase in temperature (Farrah et al, 2004), the presence of seed of the more stable phase (Azimi and Papangelakis, 2011;Dutrizac and Kuiper, 2006;Farrah et al, 2004;Hardie, 1967) and low water activity (Hardie, 1967) accelerate the transformation process.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, it was found that an increase in temperature (Farrah et al, 2004), the presence of seed of the more stable phase (Azimi and Papangelakis, 2011;Dutrizac and Kuiper, 2006;Farrah et al, 2004;Hardie, 1967) and low water activity (Hardie, 1967) accelerate the transformation process. The presence of impurities might even lead to a change in transformation mechanism, e.g., from a dissolution-precipitation based mechanism in the case of pure materials to a solid state transformation in the case of impure materials (Sirota et al, 1992). The time signifying the onset of the conversion process (otherwise known as induction time) has been reported to vary from hours to several days depending on solution composition and temperature.…”
Section: Introductionmentioning
confidence: 98%
“…There are many studies to explore the mechanism of transformation from DH to HH and to study the influence of cations and additives on HH crystal growth. Sirota et al reported that the impurities present in the FGD gypsum could change the transformation mechanism, where a solid-phase relay-race transformation without any front occurs and thus influences the shape and size of the formed HH crystals. The effects of metal ions such as Na + , K + , Mg 2+ , Cu 2+ , Al 3+ , and Fe 3+ on the crystal morphology and size of calcium sulfate whiskers in aqueous HCl solutions were also investigated. , The results revealed that Al 3+ ions resulted in bigger and shorter crystals of HH .…”
Section: Introductionmentioning
confidence: 99%